ANALISIS SKEMA KONSOLIDASI TRANSFER ANTAR PERUSAHAAN PADA ASET TIDAK LANCAR DAN TRANSFER PRICING - Maulana Iqbal Pradana; Yudha Arya Dwi Kusuma; Endang Kartini Panggiarti (Melati Institute, 2023)
The author conducted this study with the aim of analyzing intercompany transfer consolidation schemes on non-current assets and transfer pricing from previous studies, using the library research method. The benefit of this research is to increase the knowledge of readers and stakeholders related to intercompany transfer consolidation schemes on non-current assets and transfer pricing. From this study, namely the subjective conclusions regarding the consolidation scheme of intercompany transfers on non-current assets and transfer pricing based on previous research, explaining that in the implementation of all statements in financial accounting related to consolidated reports, it is necessary to make material statements about the assets owned by the merging companies or the association on intercompany transfers of non-current assets. Based on PSAK No. 65, it is explained that the ownership of assets and liabilities in each company wishing to merge needs to be recorded validly in order to minimize or material misstatement in each financial statement. Then transfer pricing is needed as a negotiation space that provides a forum for dynamics and reciprocal relations for tax authorities and taxpayers. Transfer pricing is still a common practice and activity in multinational companies. In practice, it is necessary to have an evaluation from the tax authorities so that transfer pricing practices can be minimized.